Practical application of variability analysis - Kleshnev, V. (BioRow, 2024)
Did you know that improving rowing technique consistency is a critical component of rower progression? Variations in key indicators, such as timing, angles, and force-power metrics, continuously decreased, while others, like the force curve and rowing factors, exhibited non-linear improvements. These changes were likely achieved through proper and regular coaching, an essential aspect of rower development.